Strength of silk attachment to Ilex chinensis leaves in the tea bagworm Eumeta minuscula (Lepidoptera, Psychidae) - Wolff, Jonas O. (J R Soc Interface, 2017)
Silks play an important role in the life of various arthropods. A highly neglected prerequisite to make versatile use of silks is sufficient attachment to substrates. Although there have been some studies on the structure and mechanics of silk anchorages of spiders, for insects only anecdotal reports on attachment-associated spinning behaviour exist. Here, we experimentally studied the silk attachment of the pupae and last instar caterpillars of the tea bagworm Eumeta minuscula (Butler 1881) (Lepidoptera, Psychidae) to the leaves of its host plant Ilex chinensis. We found that the bagworms spin attachment discs, which share some structural features with those of spiders, like a plaque consisting of numerous overlaid, looped glue-coated silk fibres and the medially attaching suspension thread. Although the glue, which coats the fibres, cannot spread and adhere very well to the leaf surface, high pull-off forces were measured, yielding a mean safety factor (force divided by the animal weight) of 385.6. Presumably, the bagworms achieve this by removal of the leaf epidermis prior to silk attachment, which exposes the underlying tissue that represents a much better bonding site. This ensures a reliable attachment during the immobile, vulnerable pupal stage. This is the first study on the biomechanics and structure of silk attachments to substrates in insects.